Memorial Places of Kaunas Jews and their Significance for the Local Jewish Community - Masilionytė, Jūnė (Vilnius University Open Series, 2025)
The article examines the places of memory of Kaunas City Jews, their forms, the commemorated events and people. The significance of the sites under analysis, the functions they implement and the stories they tell are also being considered. Moreover, the article presents the views of the current Jewish community in Kaunas towards those sites, both the commemoration process itself and the meaning the places of memory represent. The places are divided into several groups: commemorative plaques, monuments/memorials, street names, and street art. The groups fall into two broader categories: pre- and post-Holocaust. This allows the research to reveal what kind of memory of Kaunas Jews is created through the creation of memory places in the city.
Keywords: places of memory; Jews of Kaunas; Holocaust